Criminal Trials and Mental Disorders - Hafemeister, Thomas L. (Book collections on Project MUSE., 2019)
"The American criminal justice system is based on the bedrock principles of fairness and justice for all. In striving to ensure that all criminal defendants are treated equally under the law, it endeavors to handle similar cases in similar fashion, attempting to apply rules and procedures even-handedly regardless of a defendant's social class, race, ethnicity, or gender. Yet, the criminal justice system has also recognized exceptions when special circumstances underlie a defendant's behavior or are likely to skew the defendant's trial. One of the most controversial set of exceptions -often poorly articulated and inconsistently applied - involves criminal defendants with a mental disorder. A series of special rules and procedures has evolved over the centuries, often without fanfare and even today with little systematic examination, that lawyers and judges apply to cases involving defendants with a mental disorder. This book provides an analysis of the key issues in this dynamic interplay between individuals with a mental disorder and the criminal justice system. The volume identifies the various stages of criminal justice proceedings when the mental status of a defendant may be relevant, associated legal and policy issues, the history and evolution of these issues, and how they are currently resolved. To assist this exploration, the text also offers an overview of mental disorders, their relevance to criminal proceedings, how forensic mental health assessments are conducted and employed during these proceedings, and their application to competency and responsibility determinations."--